What does the language we use about arthritis mean to people who have osteoarthritis? A qualitative study. - Barker, K; Reid, M; Minns Lowe, C (2014)
PURPOSE: To explore the meanings and issues surrounding the use of existing medical terms for osteoarthritis from the perspective of members of the public who have consulted healthcare practitioners for arthritic symptoms and from lay people who have not sought a consultation. METHODS: Five qualitative focus groups of 6-8 respondents and six individual in-depth interviews were conducted amongst a purposive sample of men and women aged 45 years and over, with a spread of and a range of socio-economic groupings. Key terms were used as stimulus materials. Focus groups and individual interviews were audio taped, fully transcribed and underwent line by line analysis, identifying concepts and coded. RESULTS: Patients were familiar with many of the terms such as arthritis, osteoarthritis, rheumatism, inflammation, etc. but their level of comprehension varied. Most terms had little emotional impact. Terms used to describe pathophysiology elicited negative emotional impact, especially in women. Terms such as rehabilitation and "self management" were poorly understood and produced negative emotional impact. CONCLUSIONS: Healthcare professionals should not assume that patients' familiarity with medical terms correlate to understanding the term. They should be aware of the potential for negative emotional impact related to some terms. Implications for Rehabilitation Few of the existing medical terms were understood and accepted by lay participants in the way discussed and expected by health professionals. Misunderstandings, unintended meanings and negative emotional responses to terms were common within the study focus groups. Cutting the jargon and checking understanding of seemingly simple medical terms is important to improve communication with patients. As patient access to treatment notes and correspondence increases in the UK, the impact of written terms, as well as verbal, needs careful consideration and attention.